Phylogenetic relationships of the New World titi monkeys (Callicebus): first appraisal of taxonomy based on molecular evidence. Issue 1 (December 2016) - Byrne, Hazel; Rylands, Anthony; Carneiro, Jeferson; Alfaro, Jessica; Bertuol, Fabricio; da Silva, Maria; Messias, Mariluce; Groves, Colin; Mittermeier, Russell; Farias, Izeni; Hrbek, Tomas; Schneider, Horacio; et al.
Abstract Background Titi monkeys, Callicebus, comprise the most species-rich primate genus—34 species are currently recognised, five of them described since 2005. The lack of molecular data for titi monkeys has meant that little is known of their phylogenetic relationships and divergence times. To clarify their evolutionary history, we assembled a large molecular dataset by sequencing 20 nuclear and two mitochondrial loci for 15 species, including representatives from all recognised species groups. Phylogenetic relationships were inferred using concatenated maximum likelihood and Bayesian analyses, allowing us to evaluate the current taxonomic hypothesis for the genus. Results Our results show four distinctCallicebus clades, for the most part concordant with the currently recognised morphological species-groups—thetorquatus group, thepersonatus group, thedonacophilus group, and themoloch group. Thecupreus andmoloch groups are not monophyletic, and all species of the formerly recognizedcupreus group are reassigned to themoloch group. Two of the major divergence events are dated to the Miocene. Thetorquatus group, the oldest radiation, divergedc. 11 Ma; and the Atlantic forestpersonatus group split from the ancestor of alldonacophilus andmoloch species at 9–8 Ma. There is little molecular evidence for the separation ofCallicebus caligatus andC. dubius, and we suggest thatC. dubius should be considered a junior synonym of a polymorphicC. caligatus . Conclusions Considering molecular, morphological and biogeographic evidence, we propose a new genus level taxonomy for titi monkeys:Cheracebus n. gen. in the Orinoco, Negro and upper Amazon basins (torquatus group), Callicebus Thomas, 1903, in the Atlantic Forest (personatus group), andPlecturocebus n. gen. in the Amazon basin and Chaco region (donacophilus andmoloch groups).